(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Electronic health record (EHR) is patient data that store health information in digital format. Patient-centred data enables an authorized user to access the data at any time, anywhere. E-healthcare provides increasing social benefits, health benefits and reduced medical errors. The most difficult aspect of improving the use of IT frameworks in healthcare is the security issues of the systems that store health information. In the health sector, Blockchain is a revolution that may bring considerable changes in offered health services. It solves the issue of adapting and building a health care system in the healthcare community, pharmaceutical industry and insurance companies. This paper presents a framework for securing healthcare data. Public Ledger, private ledger, smart contracts and context-based access control are the basic principles behind the proposed framework. This proposed model further provides interoperability, secure storage, and reliable access to patient’s data.